Occupy in One Classroom - Shor, Ira (Radical Teacher, 2013)
2011 was an historic year of global protests. Here in New York, the Capitol of Capital, Occupy Wall Street (OWS) sustained a rebel encampment for 59 days at now-famous Zuccotti Park in the financial district. Hundreds of other occupations erupted around the United States and abroad. Occupy activists declared “Another world is possible!” and set out to build it in a small concrete park.